UPAYA GURU DALAM MENANGANI KASUS BULLYING VERBAL ANAK USIA DINI - Afina Latifah Fauziyah; Ronny Mugara; Ririn Hunafa Lestari (IKIP Siliwangi, 2021)
Early childhood education is education that is given at the age of 0-6 years. At that time, children also often experienced difficulties during their growth and development. This difficulty occurs because every child has a different development process and a different environment. Child development is influenced by several factors, including environmental factors. The environment can shape children's social-emotional development. Problems that usually arise in children's emotional social development can be seen in the presence of inappropriate children's behavior, both at home and school, one of which is bullying. Bullying is now starting to appear in kindergarten. Children at an early age are indicated and involved in verbal bullying behavior, usually have trigger factors that make the child do this. In this case, verbal bullying occurs in schools due to a lack of supervision from the teacher, lax in applying rules, and environmental factors that affect the quality of language and result in verbal bullying. This study aims to determine Kindergarten teachers' knowledge about verbal bullying. The technique used is thematic data analysis by collecting data such as observation, interviews, and documentation. The results of this study indicate the importance of handling cases of verbal bullying in early childhood, to be precise in kindergarten.Pendidikan Anak Usia dini adalah pendidikan yang diberikan pada masa usia 0-6 tahun. Di masa itu, anak juga seringkali mengalami kesulitan di masatumbuh kembangnya. Kesulitan ini terjadikarena setiap anak memiliki proses tumbuh kembang yang berbeda serta lingkungan yang berbeda. Tumbuh kembang anak dipengaruhi beberapa faktor, diantaranya adalah faktor lingkungan.Lingkungan dapat membentuk perkembangan sosial emosional anak. Permasalahan yang biasanya muncul pada perkembangan sosialemosinal anak dapat dilihat dengan adanya perilaku anak yang kurang tepat, baik dirumah maupun di sekolah, salah satunya adalah perilaku bullying. Bullyingkini mulai muncul di TK. Anak yang diusia dininya terindikasi dan terlibat dalam perilaku bullying verbal, biasanya memiliki faktor pemicu yang membuat anak melakukan hal tersebut. Dalam hal ini Perilaku bullyingverbal terjadi di sekolah karena kurangnya pengawasan dari guru, longgar dalam menerapkan aturan,serta faktor lingkungan yang mempengaruhi kualitas bahasa dan berakibat timbulnya bullyingverbal. Penelitian ini bertujuan untuk mengetahui Pengetahuan guru TK tentang bullyingverbal. Adapun teknik yang digunakan adalah analisis data tematik dengan mengumpulkan data seperti observasi, wawancara, dan dokumentasi.Hasil dari penelitian ini bahwa betapa pentingnya penanganan kasus bullyingverbal ini di kalangan usai dini tepatnya di taman kanak-kanak.